2022
DOI: 10.3390/nursrep12010021
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Clinical Training for Nursing Students during the COVID-19 Pandemic: A Scoping Review Protocol

Abstract: Background: The COVID-19 pandemic has had consequences for social, economic, cultural and educational life, affecting nursing training and practice. To date, no previous scoping reviews addressing this objective have been found. This study aims to map the literature related to changes in clinical training for nursing students during the COVID-19 pandemic. Methods: A scoping review will be carried out according to the Joanna Briggs Institute’s latest guidance regarding methodology. A set of relevant electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…The JBI latest guidance methodology guided this scoping review [ 12 , 13 , 14 ], and was reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) guidelines [ 15 ]. This review protocol has been previously published [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The JBI latest guidance methodology guided this scoping review [ 12 , 13 , 14 ], and was reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) guidelines [ 15 ]. This review protocol has been previously published [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to JBI methodology and the previously published review protocol [ 10 ], we conducted a scoping review to map the changes in clinical training for undergraduate nursing students during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…8,20 The reduced clinical time experienced by many nursing students as a result of the pandemic has made it even more difficult to practice clinical skills in real-world settings. 7,8,21 Just as one method for gaining expertise is repetition, the layering and repetition of patient tasks can be used to develop skills competency among NPRNs. 11,20 Providing NPRNs with a space in which they can repeatedly practice skills in a supportive environment, allowing them to make and learn from mistakes without fear of harming patients, has a strong positive effect on the development of NPRNs.…”
Section: Support For Clinical Skills Reviewmentioning
confidence: 99%
“…When allowed to repeatedly practice skills and receive real-time feedback, NPRNs felt more confident and prepared 8,20. The reduced clinical time experienced by many nursing students as a result of the pandemic has made it even more difficult to practice clinical skills in real-world settings 7,8,21…”
Section: Support For Clinical Skills Reviewmentioning
confidence: 99%
“…La evaluación del aprendizaje en enfermería en línea y en modalidad híbrida requiere la adaptación de los métodos tradicionales y la adopción de nuevos métodos. La evaluación basada en la simulación y la evaluación basada en la observación en línea son métodos efectivos para evaluar habilidades prácticas y clínicas (Lobão et al, 2023;Roa et al, 2021). La evaluación de la participación en foros de discusión en línea y la evaluación de proyectos individuales o en grupo también son útiles para evaluar el aprendizaje colaborativo y la aplicación del conocimiento en la práctica clínica (Hew & Cheung, 2013;Galanek & Gierdowski, 2019).…”
Section: Evaluación Del Aprendizaje En Enfermería En Línea Y En Modal...unclassified